Solvability and Profitability Ratio Analysis to Assess Financial Performance at PT. United Tractors.Tbk - Rahmatillah, Riska; Nasution, Annio Indah Lestari; Rahma, Tri Inda Fadhila (Borong Newinera Publisher, 2025)
This study aims to analyze the solvency and profitability ratios in assessing the financial performance of PT United Tractors Tbk for the period 2019–2023. The solvency ratios examined include the Debt to Equity Ratio (DER) and the Debt to Asset Ratio (DAR), while the profitability ratios consist of Return on Assets (ROA) and Return on Equity (ROE). These two categories of ratios were prioritized because they directly reflect the company’s capital structure and efficiency in generating profits, which are crucial in capturing financial resilience during periods of economic uncertainty. The analysis employed secondary data drawn from audited annual reports of PT United Tractors Tbk published by the Indonesia Stock Exchange and the company’s official website. The results indicate that solvency and profitability fluctuated throughout the study period. The sharp decline in 2020 coincided with the COVID-19 pandemic, which disrupted global demand for heavy equipment, while the improvement in ROA and ROE during 2022–2023 reflected stronger asset utilization supported by industry recovery and infrastructure expansion. Nevertheless, the increase in DER in 2023 signaled greater reliance on debt financing. This study concludes that maintaining a balance between solvency and profitability is essential for sustainable financial performance. However, since the analysis was limited to solvency and profitability ratios, future studies are encouraged to incorporate liquidity, efficiency, and market-based indicators to provide a more comprehensive picture of financial health.